Novellas and Free Voluntary Reading: an overview and some starting points for further research into practice. Issue 46 (2022) - Hunt, Steven
Abstract: In the US the use of extensive reading in Latin for school students to develop vocabulary growth and attain reading fluency is an emerging classroom practice. To meet the demand for resources, a small but growing number of teachers have started to make available self-published short Latin stories or 'novellas', designed to provide students with extensive reading material in Latin at an age-appropriate level for novice and intermediate level students. There are now over 100 such short books, written in Latin, on a variety of topics, suitable for beginner and intermediate students (typically of between one and two years taught Latin). This article contains three areas of interest: the rationale, challenges and successes of writing and using these resources in the school classroom; a snapshot survey of a range of publications, to give readers a 'flavour' of the materials; and some further reading.